PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN KEY PERFORMANCE INDICATOR KARYAWAN PT ISS AREA UNIKA ATMAJAYA - Septiana Ningtyas; Usanto Usanto; Nasib Adi Purnomo (JRIS : Jurnal Rekayasa Informasi Swadharma, 2022)
This performance measurement is a very important thing to do because all organizations need to evaluate and plan their performance to achieve organizational goals. The benefit is that workers can focus on achieving company goals and report company conditions to company stakeholders. The assessment and performance of employees' performance at this time is not good, always getting complaints from top clients about the quality obtained. A system is needed that can support decisions in evaluating employee performance. Selecting and setting KPI targets appropriately can lead the organization to potential improvements or quality improvements. This study is to analyze declining employee performance, determine key performance indicators. So that it can design an employee performance measurement system at PT ISS Indonesia